Paralomis birsteini Macpherson 1988 - Ahyong, Shane T.; Dawson, Elliot W. (Zenodo, 2006)
Paralomis birsteini Macpherson, 1988 (Figs. 5, 6) Paralomis spectabilis .—Birstein & Vinogradov, 1967: 390, figs. 1, 2— Kirkwood, 1984: 37, fig. 45 [map only].— Tkachuk, 1985: 1733 –1734, figs. A, B.— Zaklan, 2002: 773 [Ross Sea records] [not P. spectabilis Hansen, 1908]. Paralomis birsteini Macpherson, 1988a: 72 –74, figs. 4, 5a–e [type locality: Scott Island, Ross Sea, Antarctica, 67°29’S, 179°55’W].— Arana & Retamal, 1999: 101 [Bellingshausen Sea records].— Stevens, 2004: 6, 7 [part]. Neolithodes brodiei .— Thatje & Lörz, 2005: 335 [NIWA 3432 only; not N. brodiei Dawson & Yaldwyn, 1970]. Material examined. NIWA 3432, ovigerous female (cl 75.0, cw 72.9 mm), Balleny Seamount, 65°28.53–28.97’S, 161°02.88–02.75’E, 760– 750 m, TAN0402/269, RV Tangaroa , 7 Mar 2004; NIWA 24217, 1 male (cl 79.4 mm, cw 76.4 mm), near Scott I., 67°21.01–21.02’S, 179°52.68–52.34’W, 540–600 m, sled tow, TAN0602/394, 6 Mar 2006; NIWA 23842, 1 male (cl 41.4 mm, cw 40.7 mm), 1 female (cl 35.2 mm, cw 32.5 mm), both infected with Briarosaccus callosus Boschma, 1930 (Rhizocephala), near Scott I., 64°31.0–30.0’S, 171°14.0–08.0’W, 1225–1617 m, from stomach of Dissostichus mawsoni Norman, 1937, Avro Chieftain , set #24, 17 Dec 2003; NMNZ CR11000 1 male (cl 76.9, cw 73.4 mm), Ross Sea, Trip #1862, haul 147, area 88.1G, RV San Aotea , obs. S. Voice [note: specific station data not available]; NMNZ CR11001 1 male (cl 79.8, cw 74.7 mm), 1 female (cl 61.7, cw 59.4 mm), both infected with Briarosaccus callosus Boschma, 1930 (Rhizocephala), near Scott I., 68°23–21’S, 179°53–57’E, 1337– 1050 m, RV San Aotea II , trip 2010, haul 137B, on hook, B, E. Winslade, 31 Jan 2005. Diagnosis. Carapace subpentagonal, slightly longer than wide; surface glabrous, sparsely covered with small, scattered granules and short conical spines, including median gastric spine; lateral margins with short conical spines. Rostrum trispinose, broadest basally, without basal constriction. Scaphocerite with 1 or 2 short inner basal spines and 1 or 2 outer spines. ...